Field synergy principle analysis on fully developed forced convection in porous medium with uniform heat generation - Chen, G.M.; Tso, C.P.; Hung, Yew Mun (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In the presence of uniform heat source, the energy equation for forced convective heat transfer in porous medium between two parallel plates is solved for fully developed flow. Field synergy analysis is performed with emphasis on the intersection angle between the velocity vector and temperature gradient vector with the inclusion of heat generation. Maximum local intersection angle corresponds to location with the highest resistance to heat convection. Relationship between Nusselt number and field synergy for forced convection in the presence of heat generation is studied. It is necessary to define a modified intersection angle in order to compare the wall heat transfer coefficient for convective heat transfer processes with uniform heat source. (C) 2011 Elsevier Ltd. All rights reserved.